Prospective, Randomized Ex Vivo Trial to Assess the Ideal Stapling Site for Endoscopic Fundoplication with Medigus Ultrasonic Surgical Endostapler - Tae-Geun Gweon; Kai Matthes (Gastroenterology Research and Practice)
Background and Aims. Endoscopic fundoplication is an emerging technique for the treatment of gastroesophageal reflux disease (GERD). The aim of this study is to determine the ideal position of the staples in relation to gastroesophageal junction (GEJ). Methods. Ten endoscopic fundoplication procedures were performed in each group using fresh ex vivo porcine stomachs: Group A: 2 staples each at 3 cm above the GEJ and 180° apart; Group B: 2 staples at 3 cm and 90° apart; Group C: 2 staples at 4 cm and 180° apart; Group D: 3 staples at 3 cm with 90° between each staple (180° total). After the procedure, the stomach was gradually filled with water. Gastric yield pressure (GYP) was determined by detection of reflux of the water in esophagus or by rupture of staples. Results. Mean increase of GYPs (±SD) after the procedure was as follows: Group A: 16.9±8.7; Group B: 8.1±7.9; Group C: 12.2±9.4; Group D: 22.7±13.3. GYP in Group A and Group D was higher than Group B (p=0.03 and p=0.01, resp.). Conclusions. We recommend the placement of 3 staples at 3 cm distance from the GEJ, which resulted in the highest increase of GYP.